Cover Feature: A Mechanistic Dichotomy in Two‐Electron Reduction of Dioxygen Catalyzed by N, N'‐Dimethylated Porphyrin Isomers (Chem. Eur. J. 46/2020). Issue 46 (2nd August 2020) - Suzuki, Wataru; Kotani, Hiroaki; Ishizuka, Tomoya; Kojima, Takahiko
Abstract : Selective two‐electron reduction of O2 to H2 O2 has been achieved by nonplanar N, N '‐dimethylated porphyrin isomers as organocatalysts, showing the highest TON among homogeneous metal‐free catalysts. Hydrogen bonding between pyrrolic protons of reduced porphyrinoids and O2 plays an important role to control the reaction mechanism in catalytic O2 reduction. The cover art describes different mechanisms of the O2 reduction by the two isomers on the background showing shining Mt. Tsukuba in the sunset. More information can be found in the Full Paper by T. Kojima et al. on page 10480 .